2017
DOI: 10.1055/s-0043-104218
|View full text |Cite
|
Sign up to set email alerts
|

Variant PIK3R1 Hypermorphic Mutation and Clinical Phenotypes in a Family with Short Statures, Mild Immunodeficiency and Lymphoma

Abstract: Heterozygous point mutations in the GT splice donor consensus sequence of exon 11 of the PIK3R1 gene (coding for p85α, p55α, and p50α regulatory subunits of PI3K) lead to exon skipping and thereby to an aberrant protein that leaves PI3K hyperactivated. Several patients with this particular variant of PI3 kinase delta syndrome (APDS) suffering from sinopulmonary infections and lymphoproliferation have been described. (Whole exome) sequencing, evaluation of cellular and clinical phenotypes. We here report a fami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 13 publications
(16 reference statements)
0
11
0
1
Order By: Relevance
“…The clinical spectrum of APDS1, APDS2, and APDS-L is largely overlapping and consists mostly of immunological abnormalities (Table 1 ), although growth retardation has also been reported APDS2 and, less frequently, APDS1 ( 10 , 12 14 , 17 , 21 , 24 , 26 , 27 , 29 33 , 37 ). Recurrent upper and lower respiratory tract infections are the most common clinical features affecting 98% of APDS patients and often resulting in progressive airway damage.…”
Section: Clinical and Cellular Features Of Apdsmentioning
confidence: 99%
See 1 more Smart Citation
“…The clinical spectrum of APDS1, APDS2, and APDS-L is largely overlapping and consists mostly of immunological abnormalities (Table 1 ), although growth retardation has also been reported APDS2 and, less frequently, APDS1 ( 10 , 12 14 , 17 , 21 , 24 , 26 , 27 , 29 33 , 37 ). Recurrent upper and lower respiratory tract infections are the most common clinical features affecting 98% of APDS patients and often resulting in progressive airway damage.…”
Section: Clinical and Cellular Features Of Apdsmentioning
confidence: 99%
“…Because of the recurrent sinopulmonary infections, antibiotics are often given prophylactically, and immunoglobulin replacement is commonly used, although recurrent infections have been reported despite this treatment ( 15 , 20 , 26 ). Chemo- and/or radiotherapy are often used for lymphomas, a major cause of death in APDS patients (about 62% of deaths) ( 11 , 14 , 17 19 , 24 , 30 , 31 , 37 ). Beyond the treatment of these specific symptoms, hematopoietic stem-cell transplantation has proven beneficial for restoration of immune function in 67% of APDS patients receiving this therapy, which requires availability of an HLA-compatible donor and is particularly risky in the setting of EBV infection ( 10 , 14 , 15 , 18 , 24 , 31 , 34 , 36 ).…”
Section: Clinical and Cellular Features Of Apdsmentioning
confidence: 99%
“…In one E1021K APDS1 kindred ( 26 ) in which three individual affected family members exhibited a mild, intermediate, and severe spectrum respiratory infections, there seemed to be a broad association of severer phenotype with more suppressed IgG and lower class-switched memory B cells. However, this correlation was not observed in other affected families ( 2 , 27 ) and does not seem to be recapitulated in larger cohort studies. To date, no circulating biomarker has been reliably linked to respiratory phenotypes, but larger longitudinal studies may enable such correlation to be identified in future.…”
Section: Respiratory Infections In Apdsmentioning
confidence: 58%
“…While occasional case reports have highlighted significant tonsillar hypertrophy in APDS1 ( 6 , 24 ), it seems to be noted more frequently, and to be more severe in APDS2 [e.g., Ref. ( 12 , 14 , 27 , 45 )]. Tonsillar biopsies from two APDS2 patients demonstrated small B cell follicles rather than the atypical follicular hyperplasia reported in biopsies of lymph nodes/mucosal follicular hyperplasia from APDS1 ( 7 , 20 ) and APDS2 ( 14 ), but other features such as reduced mantle layers and infiltration with PD1 +ve T cells were concordant, suggesting a related immunopathogenesis.…”
Section: Non-infectious Respiratory Manifestations Of Apdsmentioning
confidence: 99%
See 1 more Smart Citation